Micro-and nanocellulose in polymer composite materials: A review - Omran A.A.B.; Mohammed A.A.B.A.; Sapuan S.M.; Ilyas R.A.; Asyraf M.R.M.; Koloor S.S.R.; Petr? M. (MDPI AG, 2023)
Agricultural robots; Agricultural wastes; Cellulose; Cellulose nanocrystals; Composite materials; Plastics industry; Sustainable development; Agriculture wastes; Bio-composites; Eco-friendly; Engineering applications; High demand; Polymer composite materials; Recent researches; Review papers; Nanocellulose